2014
DOI: 10.1146/annurev-soc-071312-145632
|View full text |Cite
|
Sign up to set email alerts
|

Political Parties and the Sociological Imagination: Past, Present, and Future Directions

Abstract: The classical sociology of parties was born alongside parties themselves. It explored their dynamic interrelationships with states and society, as well as the tensions inherent in the fact that parties are simultaneously representatives and power seekers. Despite these rich foundations, from the 1960s the sociological approach came to be narrowly identified with a one-dimensional conception of parties, and political sociologists focused their attention elsewhere. This review contributes to efforts that began i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 146 publications
0
32
0
1
Order By: Relevance
“…(2) To understand political outcomes, then, we need to deal with the political articulation of identities and goals -the supply side of politics (Beramendi, H€ ausermann, Kitschelt and Kriesi 2015;de Leon, Desai and Tu gal 2015;Mudge and Chen 2014). What the party system allows, and what parties offer, significantly conditions the kinds of alliances that can be made.…”
Section: Conflicts Of Interest Complex Identificationsmentioning
confidence: 99%
“…(2) To understand political outcomes, then, we need to deal with the political articulation of identities and goals -the supply side of politics (Beramendi, H€ ausermann, Kitschelt and Kriesi 2015;de Leon, Desai and Tu gal 2015;Mudge and Chen 2014). What the party system allows, and what parties offer, significantly conditions the kinds of alliances that can be made.…”
Section: Conflicts Of Interest Complex Identificationsmentioning
confidence: 99%
“…Many understandings of the electorate hinge on Lipset and Rokkan's theory of cleavages (), the ‘[s]trongly structured and persistent lines of salient social and ideological division among political important actors’ (Whitefield 2002 as quoted by West : 502), with the Weberian tendency to align party to clusters of coded identifiers (Mudge and Chen ). Spatially, this assumes a unitary society (congruent with, but distinct from, the state) to be cleaved; it also situates a society's specific cleavages within its historical political–economic development, drawing on historical materialism to account for the emergence of divergent regional interests that persist over time: so ‘different geographical and historical experiences will produce different lines of cleavage’ (West : 502).…”
Section: Political Parties In Traditional Electoral Geographymentioning
confidence: 99%
“…Agnew (: 130) has suggested that electoral geography was left behind because ‘so much of the best new thinking has come from a political‐intellectual left inclined to regard elections as exercises in a bourgeois politics they would like to put behind them’ (also true of political sociology, see Mudge and Chen ; Leon ). Yet, it is possible to believe that elections matter without reducing politics to ‘just elections’.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In seeking to fill these lacunae, political scientists would benefit from engagement with the sociological literature on parties. SeeMudge and Chen (2014).…”
mentioning
confidence: 99%